2023
DOI: 10.1001/jamaophthalmol.2023.1467
|View full text |Cite
|
Sign up to set email alerts
|

Disparities Associated with Discharge Patterns in Firearm-Associated Ocular Trauma

Abstract: ImportanceFirearm injuries are associated with devastating visual outcomes. Several studies have demonstrated disparities in trauma care and discharge to rehabilitation and other advanced care facilities (ACFs) due to race and ethnicity and insurance status. The identification of possible disparities in disposition of patients admitted with firearms-associated ocular injuries (FAOIs) is a crucial step in moving toward health equity.ObjectiveTo describe disposition patterns following admission for FAOI trauma.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Black and Hispanic patients were less likely to be allocated to advanced care facility than their White counterparts. This was noted for all insurance coverage and injury severity levels [ 55 ]. Further research that illuminates specific factors associated with increased mortality of minority patients admitted with very severe injury is warranted.…”
Section: Discussionmentioning
confidence: 83%
“…Black and Hispanic patients were less likely to be allocated to advanced care facility than their White counterparts. This was noted for all insurance coverage and injury severity levels [ 55 ]. Further research that illuminates specific factors associated with increased mortality of minority patients admitted with very severe injury is warranted.…”
Section: Discussionmentioning
confidence: 83%
“…In the field of ocular trauma, disparities in discharge patterns and visual outcomes have been reported in research. [1][2][3] A prior study 2 investigating older patients with ocular trauma found that Black, Hispanic, male, and self-paying patients were disproportionately discharged home. Knowing that ocular trauma due to gunshot wounds can lead to longterm visual damage outcomes, 3 in-depth analyses of patient discharge patterns after firearm-associated ocular injury (FAOI) can elucidate underlying disparities in care.A recent study in this issue of JAMA Ophthalmology by Mike et al 1 reports disparities in discharges to an advanced care facility (ACF) after being admitted with FAOI in the US.…”
mentioning
confidence: 99%